An Exploratory Study of English Teachers: The Use of Social Media for Teaching English on Distance Learning - Ubaedillah Ubaedillah; Damar Isti Pratiwi; S. Thoriqul Huda; Dwi Agung Kurniawan (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
This study was conducted to determine how English teachers used social media to teach English. An exploratory study was used in this study to look into a detailed and in-depth analysis of the use of social media in English language learning by Cirebon junior high school teachers. This study used purposive sampling from 43 English teachers at Cirebon junior high schools. Ten teachers (five male and five female) have been chosen. In about 20 to 30 minutes, each participant was asked the questions. The researcher recorded all of the conversations during the interview session as part of the data collection process. Whatsapp, Facebook, Instagram, Tiktok, and YouTube are the most popular social media platforms with strong categorized. Whatsapp has a higher presentation value than other social media types. There were five themes identified as a result of the interview session of the teacher's perceptions of social media used on distance Learning; 1) Kinds of social media, 2) Activities, 3) Motivation, 4) Improving students English language skills, and 5) Effectiveness.